2021
DOI: 10.3390/app11167507
|View full text |Cite
|
Sign up to set email alerts
|

Non-Surgical Touch-Up with Hyaluronic Acid Fillers Following Facial Reconstructive Surgery

Abstract: The use of hyaluronic acid (HA) injectable fillers has become increasingly widespread in facial recontouring and rejuvenation. We report our experiences to emphasize the role of HA fillers as tools beyond aesthetic treatments in cases of post-surgical facial sequelae. HA fillers are generally used for aesthetic rejuvenation, but one potential new horizon could be their application in trauma, reconstructive, and craniofacial surgery. This study was conducted retrospectively, evaluating medical reports of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 134 publications
(212 reference statements)
0
16
0
Order By: Relevance
“…Hyaluronic acid is currently the leading dermal filler type for cosmetic use due to both its efficacy and improved safety (low allergenicity, longevity, and ability to be reversed). Hyaluronic acid filler in previous atrophic scar studies showed high treatment satisfaction with only mild transitory erythema, bruising, and mild to moderate pain during injection 1‐7 . Goodman and Broek published the use of a modified tower technique, creating vertical posts through a retrograde injection bringing the HA up into the superficial dermis with resolution of over 70% of the scars 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyaluronic acid is currently the leading dermal filler type for cosmetic use due to both its efficacy and improved safety (low allergenicity, longevity, and ability to be reversed). Hyaluronic acid filler in previous atrophic scar studies showed high treatment satisfaction with only mild transitory erythema, bruising, and mild to moderate pain during injection 1‐7 . Goodman and Broek published the use of a modified tower technique, creating vertical posts through a retrograde injection bringing the HA up into the superficial dermis with resolution of over 70% of the scars 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Hyaluronic acid filler in previous atrophic scar studies showed high treatment satisfaction with only mild transitory erythema, bruising, and mild to moderate pain during injection. 1 , 2 , 3 , 4 , 5 , 6 , 7 Goodman and Broek published the use of a modified tower technique, creating vertical posts through a retrograde injection bringing the HA up into the superficial dermis with resolution of over 70% of the scars. 2 This paper also noted the importance of injection of the superficial dermis to create blebs that could then be massaged out, 2 something that should not be done with PMMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for non-surgical procedures to correct blemishes has grown considerably in recent years, and the injection of hyaluronic acid (HA) represents the second most common procedure after the injection of botulinum toxin, with an increase in demand of 60% from 2014 to 2018 [29]. Hyaluronic acid-based treatments offer a valid alternative to some surgical interventions, with immediate results, little or no recovery times, and the possibility to repeat the procedure if needed [30][31][32]. Treatment options for the tear-trough deformity can be surgical [33], alloplastic implant [34], or autologous fat grafting [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PEGDE was used as a cross-linker for HA-itaconic acid film which is a bioadhesive matrix used for topical drug delivery in ophthalmology [9]. Further, PEGDE crosslinked HA fillers were utilized for facial rejuvenation and aesthetic enhancement following facial reconstructive surgery [10]. In such cases, PEGDE is used as a cross-linking agent to allow the formation of C-O-C bonds, thus increasing the stability of a hydrogel.…”
Section: Introductionmentioning
confidence: 99%